EFL/ESL Teachers' and Students' Perceptions and Practices of Written Feedback in a Higher Education Context - Abderrahim Mamad; Tibor Vígh (Universidad Nacional de Colombia, 2024)
This systematic review focused on higher education teachers' and students' perceptions and practices of written feedback, as well as their relationships and differences in English as a foreign/second language and academic writing. This study aimed to identify empirical studies, describe their characteristics, summarize the findings, and make recommendations for future research. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses protocol was used. Electronic searches produced 2,398 references, of which 30 articles met the inclusion criteria. Studies primarily focused on students' perceptions, with few concentrating on students' and teachers' reported practices and the relationships between their perceptions and practices. This review suggests that future research should focus on multiple comparisons between teachers' and students' perceptions and practices of written feedback.